2019
DOI: 10.3390/ijms20133133
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis of Aedes aegypti Innate Immune System in Response to Ingestion of Chikungunya Virus

Abstract: Aedes aegypti (L.) is the primary vector of emergent mosquito-borne viruses, including chikungunya, dengue, yellow fever, and Zika viruses. To understand how these viruses interact with their mosquito vectors, an analysis of the innate immune system response was conducted. The innate immune system is a conserved evolutionary defense strategy and is the dominant immune system response found in invertebrates and vertebrates, as well as plants. RNA-sequencing analysis was performed to compare target transcriptome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 60 publications
4
18
0
Order By: Relevance
“…Distinct mosquito gene expression profiles underpinned infection response at different ambient temperatures, both in the absolute number of DEGs but also their gene identities. Similar to our findings for 28°C, a recent study of mosquitoes held at 30°C found a larger number of DEGs expressed at 3 dpi in response to CHIKV [ 35 ]. However, exposure to 32°C in our study elicited a surprisingly low number of genes being expressed in response to CHIKV compared with control uninfected mosquitoes, particularly at the earlier time point.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Distinct mosquito gene expression profiles underpinned infection response at different ambient temperatures, both in the absolute number of DEGs but also their gene identities. Similar to our findings for 28°C, a recent study of mosquitoes held at 30°C found a larger number of DEGs expressed at 3 dpi in response to CHIKV [ 35 ]. However, exposure to 32°C in our study elicited a surprisingly low number of genes being expressed in response to CHIKV compared with control uninfected mosquitoes, particularly at the earlier time point.…”
Section: Discussionsupporting
confidence: 91%
“…Using a literature review, we identified 10 additional gene families, resulting in a total of 37 gene families implicated in mosquito immunity (electronic supplementary material, table S4), producing a final list of 998 genes. The list was divided into classical or non-classical components (electronic supplementary material, tables S5 and S6) [ 26 35 ]. Genes already identified and directly involved in humoral and cellular immune response were considered as classical immune genes [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Distinct mosquito gene expression profiles underpinned infection response at different ambient temperatures, both in the absolute number of DEGs but also their gene identities. Similar to our findings for 28 °C, a recent study of mosquitoes held at 30 °C found a larger number of DEGs expressed at 3 dpi in response to CHIKV [37]. However, exposure to 32 °C in our study elicited a surprisingly low number of genes being expressed in response to CHIKV compared to control uninfected mosquitoes, particularly at the earlier time point.…”
Section: Discussionsupporting
confidence: 88%
“…The first step in eliciting an immune response is the recognition of pathogens by pattern recognition receptors [40]. Similar to previous studies [3739, 41], we identified diverse PRR genes being differentially expressed in our study, including CLIP-domain serine protease family B, FREP, LRR, leucine-rich transmembrane proteins, CTLs, TEP and Galectins. However, we did not find any PRR DEGs common across all temperature treatments at 3 dpi, while at 7 dpi only CLIPD6 was shared.…”
Section: Discussionsupporting
confidence: 82%
“…In total, we found 18 unique genes, representing the predicted targets for 12 out of the 14 miRNAs from our study, which were shown to be significantly modulated in different studies involving whole Ae. aeygpti , midgut and carcass with CHIKV, DENV, WNV, or ZIKV at 1 dpi, 2 dpi, 4 dpi, 7 dpi, or 14 dpi [ 102 , 103 , 104 , 105 ]. We focused on significantly downregulated transcripts that were predicted as targets for the significantly upregulated miRNAs in this study.…”
Section: Resultsmentioning
confidence: 99%